Desenvolvimento de um procedimento Micro-QuEchERS para determinação de pesticidas em vinhos - Dagli, Fernando Jorge Geraldes (2018)
The great consumption of wine around the world, associated with the fact that the grapes are produced using pesticides, brings an alert to the con-sumers, since these toxic substances remain present in the final product, mak-ing their residual analysis important in order to ensure compliance with current legislation on the subject. Many techniques have been employed in such de-terminations, from the preparation of the sample, separation of the analytes, to their detection. The QuEChERS method suggests several advantages in the preparation of samples. However, large quantities of solvents are employed during its application. The miniaturization of the method showed that it is pos-sible to obtain satisfactory results in the determination of the imidacloprid, car-bofuran and tebuconazole pesticides in white and rosé wines, using amounts of solvents and salts 20 times smaller than the original method, coinciding with the green chemistry proposals. The separation of these analytes was achieved by the use of high performance liquid chromatography coupled to an ultraviolet spectrometry detector with diode array (HPLC-DAD). Using this system, after optimization of the sample preparation method, recoveries above 80% were achieved for the three pesticides and, within the values of maximum residue limits (MRLs) established in the current legislation, the technique proved capa-ble of obtaining results that guarantee their respect.